Melting of Iron Explored by Electrical Resistance Jump up to 135 GPa - Mingqiang Hou; Jin Liu; Youjun Zhang; Xueyan Du; Hongliang Dong; Limin Yan; Junyue Wang; Lin Wang; Bin Chen (Geophysical Research Letters)
Abstract The melting temperature (Tm) of iron at megabar pressures constrains the Earth's core temperature structure and dynamics. Previous experimental studies demonstrated large discrepancies in Tm at high pressures. We used the intrinsic resistance discontinuity across solid‐liquid transition as a melting criterion to study the melting behavior of iron in laser‐heated diamond anvil cells. The resistance jump is sensitive to the incipient melting, capable of detecting the emergence of less than 2 vol.% melts. We found a high melting curve of iron at 30–135 GPa, but a relatively low‐transition temperature of the slow‐fast recrystallization. The determined Tm of iron is 4306(±300) K at the core‐mantle boundary (CMB) pressure in good agreement with the static and shockwave experimental results by Anzellini et al. (2013, https://doi.org/10.1126/science.1233514) and Li et al. (2020, https://doi.org/10.1029/2020gl087758). The high melting point of iron implies a high and steep geothermal gradient and influences a heat flow across the CMB.